Distribution of Cryptosporidium species isolated from diarrhoeic calves in Japan. (October 2020) - Kabir, Mohammad Hazzaz Bin; Itoh, Megumi; Shehata, Ayman Ahmed; Bando, Hironori; Fukuda, Yasuhiro; Murakoshi, Fumi; Fujikura, Atsushi; Okawa, Hiroaki; Endo, Takuto; Goto, Akira; Kachi, Masayuki; Nakayama, Toshie; et al.
Abstract: Cryptosporidium spp. are enteric protozoan parasites that infect a wide range of hosts including humans, and domestic and wild animals. The aim of this study was to molecularly characterize the Cryptosporidium spp. found in calf faeces in Japan. A total of 80 pre-weaned beef and dairy calves' diarrhoeic faecal specimens were collected from nine different prefectures in Japan. A nested polymerase chain reaction targeting the small subunit 18S rRNA and GP60 genes were used to detect the Cryptosporidium genotypes and subtypes. 83.8% (67 out of 80) of the specimens were positive for Cryptosporidium spp.; Cryptosporidium was found in both beef and dairy calves. Cryptosporidium parvum was the predominant species, detected in 77.5% (31/40) of beef calves and 80% (32/40) of dairy calves. Cryptosporidium bovis was also detected, 5.0% (2/40) of dairy calves, and C. ryanae was also found 2.5% (1/40) of dairy calves. One mixed-species infection, 2.5% (1/40) was detected in a beef calf having C. parvum, and C. ryanae . We detected the most common subtype of C. parvum (i.e., IIaA15G2R1), as well as other subtypes (i.e., IIaA14G3R1, IIaA14G2R1, and IIaA13G1R1) that have not previously been detected in calves in Japan. Our results demonstrate the widespread diversity of Cryptosporidium infection in calves in Japan. Highlights: Cryptosporidium parvum is a widely distributed Cryptosporidium species in pre-weaned diarrhoeic calves in Japan. Three different C. parvum subtypes, namely IIaA14G3R1, IIaA14G2R1, IIaA13G1R1, were detected for the first time in Japan. The widespread diversity of Cryptosporidium infection is shown in calves in Japan.